Small Cell Neuroendocrine Carcinoma of the Breast: Report of a Case - Parali, Ayse; Ozkal, Afife; Gungor, Fulya Buse; Melemez, Mukaddes Kubra; Simsek, Betul; Ozmeral, Kubra; Eren, Tunc; Aydın, Abdullah; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2018)
Small cell neuroendocrine tumor of the breast is a rare clinical condition. Although there’s limited information about this entity, it is considered to have a poor prognosis. A 44-yearold woman presented with a 5 cm mass in the lower-outer quadrant of the right breast and its tru-cut biopsy results revealed a neuroendocrine tumor. She underwent a modified radical mastectomy followed by neoadjuvant chemotherapy and radiotherapy. She remains disease-free at the end of her 6-months follow-up period. International Journal of Human and Health Sciences Vol. 02 No. 02 April’18. Page : 98-101